Effect of rare earth Ce on high temperature oxidation resistance and corrosion resistance of cobalt-based alloys - DING Rui; ZHANG Liang; WU Wenheng (Fenmo yejin jishu)
Cobalt-based alloys containing different mass fractions of rare earth element Ce (0, 0.04%, 0.14%, 0.19%) were prepared by selective laser melting technology. The influence of Ce element on high-temperature oxidation resistance and corrosion resistance was systematically discussed. The microstructure and phase composition of the alloys were analyzed by scanning electron microscopy, X-ray diffractometer, high-temperature oxidation weight gain experiment, and electrochemical test. The oxidation kinetics behavior of the alloys, the morphology of the oxide films, and the corrosion resistance of the alloys were also studied. The results show that the alloys with the mass fraction of 0.14% Ce have the best oxidation resistance at 900 ℃, with the lowest oxidation weight gain (only 0.179 mg·cm−2 for 100 h). The oxide film grains are significantly refined and dense, which are mainly composed of the dense Cr2O3 layers and the outermost CoCr2O4 spinel phases. The electrochemical tests show that the effect of Ce on the corrosion resistance of the alloys is not clear.